- #1

- 8

- 0

## Homework Statement

The projection of the vector V onto (a,b) = (a,b)

The projection of the vector V onto (-b,a) = (-b,a)

Describe V in terms of a and b

## Homework Equations

## The Attempt at a Solution

I let V=(x,y) then place that into the projection equation for each to get:

[(x,y)(a,b)/(a,b)(a,b)](a,b) = [ax+by/a^2+b^2](a,b)=(a,b)

[(x,y)(-b,a)/(-b,a)(-b,a)](-b,a) = [-bx+ay/b^2+a^2](-b,a)=(-b,a)

After seeing this I realized that:

k(V)=V so k has to equal 1

so both [ax+by/a^2+b^2] and [-bx+ay/b^2+a^2] should eqaul 1

Then I let:

[ax+by/a^2+b^2]=[-bx+ay/b^2+a^2]

the denominators cancel each other out and I'm left with

ax+by=-bx+ay

After that I solved for y to get y=(a^2+b^2-ax)/b

Subsituting that in I get:

[-bx+a[(a^2+b^2-ax)/b]/b^2+a^2]

Reducing and all that other good stuff I finally get x=[a^2+b^2-(a^3/b)+[(ab^2)/2]]/[(a^2)/b]-b]

I am unaware if I am doing this correctly, maybe it's just how it looks that is throwing me off. Any advice or help would be greatly apperciated. THanks

Last edited: